The Influence of Series Picture on the Students’ Writing Recount Text Ability - . Kurniawati; Yanuar Dwi Prastyo; Imam Subari (International Conference on Education and Language (ICEL), 2013)
The purpose of teaching learning English is to develop four language skills, such as, listening, reading, speaking, and writing. The students are expected to be able to master the four skills. So that they can communicate effectively in English, either in spoken or written. But many students still often find difficulties in the learning process, especially in learning writing. The teachers must be able to find out a strategy in learning English included in writing skill. The English teachers can use some interesting methods in their teaching process, such as, using series picture. It can be used to motivate the students in developing their vocabularies to express their ideas. This research is aimed at finding out the influence of series picture on the students’ writing recount text ability. In this research, the writer used two classes as the experimental and control class. Based on the result of the data analysis which used t-test formula, it was found that there was influence of using series picture towards students’ writing ability in recount text at the second semester of grade eleventh at SKM N 1 Tanjungsari South Lampung in academic year 2011-2012. In significant level of 0.05, t-test is higher than t-table, t-test > t-table = 3.75 > 1.999. It also can be seen from the score of experimental class is 9.73 and score of control class is 7.61. It means that the score of experimental class was higher than control class